Pengaruh Tingkat Kematangan Buah Pepaya (Carica papaya L.) Sebagai Bahan Tambahan Terhadap Tingkat Kesukaan Saus Tomat: The Effect of Papaya (Carica papaya L.) Ripeness Level as an Additive on Tomato Sauce Likability - Ansar Ansar; Agus Salim Syam; Nurul Mukhlishah; Aziza Noor Sheha Arfah (Jurnal Food And Forest, 2026)
Tomato sauce is a popular food product, but the price of its main raw material often fluctuates. Papaya (Carica papaya L.) has the potential to be an economical additive (extender), but its ripeness level is thought to affect product acceptability. This study aimed to analyze the effect of adding papaya with different ripeness levels (unripe vs. ripe) on the level of liking of tomato sauce. This study used a Completely Randomized Design (CRD) with three treatments: P0, P1, and P2. The level of liking was measured through a hedonic test by 30 untrained panelists on the attributes of color, aroma, taste, texture, and overall acceptability using a scale of 1-9. Data were analyzed statistically using the Kruskal-Wallis test followed by the Mann-Whitney test. The results showed that the treatments had a significant effect (p<0.05) on all sensory attributes. Tomato sauce with the addition of ripe papaya (P2) achieved the highest preference scores for color (7.80), aroma (7.55), taste (8.10), and overall acceptability (8.05). Meanwhile, the control sauce (P0) excelled in texture (7.90). The addition of unripe papaya (P1) tended to produce the lowest scores for almost all attributes, especially taste (6.20). It was concluded that the addition of 30% ripe papaya was the best treatment because it produced the tomato sauce most preferred by the panelists.